2022
DOI: 10.1002/erv.2930
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the eating disorder service experiences of autistic and non‐autistic women in the UK

Abstract: Objective: Qualitative studies report that autistic women have poor experiences when being treated for an eating disorder (ED) and express that ED services are not appropriately tailored to meet their needs. It is unclear whether their experience differs to other women accessing ED services. The aim of the current study was to compare autistic and non-autistic women's ED illness history and experiences in ED services. Method: An online survey about ED illness history and their experience with ED treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Even when practitioners were aware of an autism diagnosis, participants felt that autism was not taken into consideration and that they were perceived as ‘too complex’ for services [ 76 ]. Autistic individuals are referred to and access a broader range of ED treatment settings compared to their non-autistic peers [ 78 ], suggesting that these settings do not know how to manage co-occurring EDs and autism.…”
Section: Systemic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when practitioners were aware of an autism diagnosis, participants felt that autism was not taken into consideration and that they were perceived as ‘too complex’ for services [ 76 ]. Autistic individuals are referred to and access a broader range of ED treatment settings compared to their non-autistic peers [ 78 ], suggesting that these settings do not know how to manage co-occurring EDs and autism.…”
Section: Systemic Factorsmentioning
confidence: 99%
“…Cognitive behaviour therapy for EDs (CBT-E) is a common treatment approach for adults with EDs [ 79 ]. Autistic individuals reported that CBT was not helpful for them because it presumed pre-existing skills that these individuals did not have [ 76 , 78 ]. For example, one autistic woman described that she was not able to generalize the skills that she had learned because she did not know that this was the goal of treatment [ 76 ].…”
Section: Systemic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with AN and higher levels of autistic traits also had longer illness durations [ 10 ]. Autistic women with AN reported accessing a broader range of ED treatments than non-autistic women, suggesting they have difficulty accessing treatments that work [ 11 ]. Autistic women also rated various aspects of ED treatment as less beneficial than non-autistic women [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autistic women with AN reported accessing a broader range of ED treatments than non-autistic women, suggesting they have difficulty accessing treatments that work [ 11 ]. Autistic women also rated various aspects of ED treatment as less beneficial than non-autistic women [ 11 ]. When followed up over a 30 year period, autistic adolescents with AN had worse outcomes than non-autistic adolescents in terms of mental state, independence from their families, social contact, and employment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%